Phenotypic Changes of Peripheral γδ T Cell and Its Subsets in Patients With Coronary Artery Disease - Li, Yan; Jiang, Silin; Li, Jiawei; Yin, Mengzhuo; Yan, Fuxin; Chen, Yuyuan; Chen, Yan; Wu, Tongwei; Cheng, Mengliang; He, Yihua; Liang, Hongbin; Yu, Hang; et al. (Frontiers in Immunology, 2022)
Coronary atherosclerotic heart disease (CAD) is a chronic inflammatory cardiovascular disease with high morbidity and mortality. Growing data indicate that many immune cells are involved in the development of atherosclerosis. However, the immunological roles of γδ T cells in the initiation and progression of CAD are not fully understood. Here, we used flow cytometry to determine phenotypical changes of γδ T cells and their subpopulations in peripheral blood samples collected from 37 CAD patients. The Pearson correlation coefficient was used to analyze the relationship between the clinical parameter (serum LDL-C level) and the changes of immunophenotypes of γδ T cells. Our results demonstrated that the frequencies and absolute numbers of total γδ T cells and Vδ2+ T cells were significantly decreased in CAD patients when compared to healthy individuals. However, the proportion of Vδ1+ T cells was much lower in CAD patients than that of healthy individuals. Most importantly, a significant alteration of the Vδ1/Vδ2 ratio was found in CAD patients. In addition, a series of surface markers that are associated with costimulatory signals (CD28, CD40L, CD80, CD86), activation levels (CD69, CD25, HLA-DR), activating NK cell receptors (NKp30, NKp46, NKG2D) and inhibitory receptors (PD-1, CTLA-4, PD-1, Tim-3) were determined and then analyzed in the total γδ T cells, Vδ2+T cells and Vδ2-T cells of CAD patients and healthy individuals. The data demonstrated that immunological activities of total γδ T cells, Vδ2+T cells, and Vδ2-T cells of CAD patients were much lower than those in healthy individuals. Moreover, we found that there were positive correlations between the serum LDL-C levels and frequencies of CD3+γδ+ T cells, CD69+Vδ2+T cells, NKG2D+Vδ2+T cells, and NKp46+Vδ2+T cells. By contrast, there was an inverse correlation between the levels of serum LDL-C and the frequencies of CD69+Vδ2-T cells and NKp46+Vδ2-T cells. Accordingly, these findings could help us to better understand the roles of γδ T cells in the CAD, and shed light on the development of novel diagnostic techniques and therapeutic strategies by targeting γδ T cells for CAD patients.